Ujaran Kebencian Terhadap Pejabat Publik Dalam Media Sosial: Kajian Pragmatik Pendekatan Gender - Aris Widodo, Lukman; , Prof. Dr. Harun Joko Prayitno, M.Hum; , Prof. Dr. Abdul Ngalim, MM., M.Hum (2017)
The objectives of the study are to identify the different types, describing the strategy, and describe the characteristics in the form of hate speech by men and women toward public officials in social media. The types of the research is qualitative research. The object of the research in the form of differences hate speech, politeness strategies, and the characteristics of hate speech in social media. The method of collecting data through simak method, followed by advanced technique I in the form of note technique, advanced technique II in the form of documentation technique. The technique of analyzing data using padan method and agih method. The result of this study found 12.5% provoking religious, 15% provoking leadership, and 7.5% provoking threat. Found 17.5% defamation of religion, 7.5% defamation of leadership, and 2.5% defamation of threat. Found of 7.5% religious blasphemy, 22,5% leadership blasphemy and 7.5% threat blasphemy. Marker lingual politeness speech on hate speech, which is marked by intonation news. On the politeness strategy used in the hate speech by men and women toward public officials in social media found some forms of direct and indirect speech. The form of direct speech is found as much as 60% and the form of indirect speech is found as much as 40%. Characteristic types of hate speech by men and women found form of hate speech provoking with direct and indirect speech, in the form of hate speech hate speech found direct and indirect speech, then on the form of hate speech shroud found direct and indirect speech.